The Impact of Multiple Comorbid Mental Health Disorders on Health-related Quality of Life Following ACDF. Issue 10 (December 2020) - Mangan, John J.; Tadley, Madeline; Divi, Srikanth N.; Stull, Justin D.; Goyal, Dhruv K.C.; McKenzie, James C.; Casper, David S.; Galetta, Matthew S.; Kaye, Ian D.; Kurd, Mark F.; Woods, Barrett I.; Radcliff, Kris E.; et al.
Abstract : Study Design: Retrospective comparative study. Objective: The goal was to determine whether comorbid depression and/or anxiety influence outcomes after anterior cervical discectomy and fusion (ACDF) for patients with degenerative cervical pathology. Background Data: The role preoperative mental health has on patient reported outcomes after ACDF surgery is not well understood. Methods: Patients undergoing elective ACDF for degenerative cervical pathology were identified. Patients were grouped based on their preoperative mental health comorbidities, including patients with no history, depression, anxiety, and those with both depression and anxiety. All preoperative medical treatment for depression and/or anxiety was identified. Outcomes including Physical Component Score (PCS-12), Mental Component Score (MCS-12), Neck Disability Index (NDI), Visual Analogue Scale neck pain score (VAS Neck ), and Visual Analogue Scale arm pain score (VAS Arm) were compared between groups from baseline to postoperative measurements using multiple linear regression analysis—controlling for factors such as age, sex, and body mass index, etc. A P -value <0.05 was considered statistically significant. Results: A total of 264 patients were included in the analysis, with an average age of 53 years and mean follow-up of 19.8 months (19.0–20.6). All patients with a diagnosis of depression or anxiety also reported medical treatment for the disease. The group with no depression or anxiety had significantly less baseline disability than the group with 2 mental health diagnoses, in MCS-12 ( P =0.009), NDI ( P <0.004), VAS Neck ( P =0.003), and VAS Arm ( P =0.001) scores. Linear regression analysis demonstrated that increasing occurrence of mental health disorders was not a significant predictor of change over time for any of the outcome measures included in the analysis. Conclusions: Despite more severe preoperative symptoms, patients with a preoperative mental health disorder(s) demonstrated significant improvement in postoperative outcomes after ACDF. No differences were identified in postoperative outcomes between each of the groups. Level of Evidence: Level III.